SANKSI PIDANA TERHADAP MUCIKARI YANG MEMASARKAN PROSTITUSI MELALUI SARANA MEDIA ONLINE (STUDI KASUS: PUTUSAN PENGADILAN NEGERI DENPASAR NO. 642/PID.B/2015/PN.DPS.) - Calvin .; Dian Andriawan Daeng Tawang (Jurnal Hukum Adigama, 2018)
Cybercrime is a crime involving online media means as an object to carry out the crime. Cybercrime itself also has many forms that one of them is cybersex, cybersex is a crime that violates the offense of decency in which the crime involves the medium of online media. For example the case in this case is a crime in the form of selling the services of online prostitution whose perpetrator is a pimp, pimps in this case means the person who acts as a caregiver and / or owner of commercial sex workers. Most cases of online prostitution crime are in the bali area of Denpasar. Online prostitution crime itself has violated Article 45 paragraph 1 of Law Number 19 Year 2016 on Information and electronic transactions. But the panel of judges in its decision only decided in the form of articles contained in the Criminal Code so that the imposition of criminal sanctions on the defendant became very light and made the perpetrators became not afraid of the relatively light criminal sanctions. So that the law in Indonesia becomes very weak and from the light criminal law sanction makes the perpetrators continue to do the crime action. When viewed from the lex specialist derogate legi generalie principle stating the special provisions to override general provisions, meaning that the Act should be used is Law No. 19 of 2016 on Information and Electronic Transactions.